Role of Lipiodol® lymphangiography in the diagnosis and management of post-operative chylous ascites - Litchinko, Alexis; Monnard, E.; Tappero, C.; Egger, B. (Frontiers in Radiology, 2025)
IntroductionChylous ascites, defined as the pathological accumulation of lymphatic fluid in the peritoneal cavity, presents significant challenges due to the lack of standardized treatment protocols. This study evaluates the dual diagnostic and therapeutic role of Lipiodol® lymphangiography in managing post-operative chylous ascites, with a focus on its potential to inform modern interventional strategies.Materials and methodsA retrospective review was conducted of four patients treated for post-operative chylous ascites at our institution between 2017 and 2023. These patients, who developed refractory chylous ascites following oncological surgeries involving radical lymphadenectomy, underwent Lipiodol® lymphangiography. Diagnostic findings, therapeutic outcomes, and procedural details were analyzed.ResultsLipiodol® lymphangiography demonstrated a dual function, providing precise anatomical localization of lymphatic leaks while facilitating therapeutic embolization due to its viscosity. All four patients achieved resolution of chylous ascites following lymphangiography alone, with a 100% success rate after the first attempt. No complications were reported within 30 days post-procedure, underscoring the safety of this minimally invasive technique.ConclusionsLipiodol® lymphangiography represents an effective diagnostic and therapeutic modality for post-operative chylous ascites, offering a minimally invasive alternative to traditional surgical interventions. By elucidating the pathway for both diagnosis and treatment, this study highlights its potential role in establishing standardized protocols for managing this complex condition.